Review of "The Client Connection: How Advisors Can Build Bridges That Last" - Jack Reilley (Journal of Financial Therapy, 2010)
In their book titled The Client Connection: How Advisors Can Build Bridges That Last, Olivia Mellan and Sherry Christie have done an outstanding and comprehensive job of addressing important current issues affecting the financial planning profession. Although not a long book, the authors are able to comprehensively address topics associated with client relationship building. Their writing style is accessible and offered for consideration in a context appropriate to novice and seasoned professionals alike. While there are 23 chapters in total, the material is organized under seven headings that form the overarching framework for the material presented. Overall, in the opinion of this reviewer, the authors did a nice job of connecting various ideas and concepts that might otherwise have seemed disconnected without this framework. The following review provides a glimpse of each section of the book.